Uncertainty Assessment of the Remaining Volume of an Offshore Gravity Fish Cage - Zhongchi Liu; C. Guedes Soares (Journal of Marine Science and Engineering, 2024)
The volume of a gravity cage is greatly reduced under a current due to the flexible structure, which affects the growth and health of the fish. Thus, an accurate assessment of cage volume is essential to determine the number of fishes in the cage. In this study, firstly, a numerical model was built to study the cage volume reduction of gravity cages due to the flexible net deformation when subjected to uniform flow. The remaining volume was calculated and compared with earlier experiments. Even though the flow velocity reductions were considered according to the data from previous experiments, the differences between the results from the numerical calculation and the towing tests are still significant. The physical model tests were treated as the reference value to investigate the uncertainty of the model results. Both the velocity-independent model error and velocity-dependent model error were calculated. With the help of the error models, the uncertainty of the remaining volume can be predicted. In addition, the velocity-dependent model error performs better in evaluating the uncertainty of the numerical calculation of the remaining culturing volume. Overall, the results show that the numerical model assisted by the model errors can calculate the cage volume accurately.